Growth regimes, dominant social blocs and growth strategies: towards varieties of export-led growth regimes and strategies in Turkey and Poland - Ümit Akcay; Benjamin Jungmann (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2023)
This paper aims to contribute to the literature on growth regimes by combining an operationalization of growth regimes based on growth contributions and sectoral financial balances with an analysis of dominant social blocs (DSBs). We propose the concept of a growth strategy to bridge the political and actor-oriented sphere with the macroeconomic sphere. We employ this framework to analyze the cases of Poland and Turkey. The study identifies a transition from a domestic demand-led regime to a weakly export-led regime in Poland, while Turkey experienced a shift from a domestic demand-led regime to a debt-led private demand regime and subsequently towards a weakly export-led regime, too. Both countries' new DSBs pursue export-led growth strategies, but Poland's strategy focuses on non-price competitiveness while Turkey relies on price competitiveness. We lay out the differences between the strategies in terms of policies and the capital fractions supporting them.
Keywords: B52; E65; E66; F43; O43; P16; P52; 330; post-Keynesian macroeconomics; comparative political economy; growth regimes; growth strategies; Poland; Turkey